Reações de 3-trialoacetil-4,5-diidrofuranos e 5-trialoacetil-3,4-diidro-2H-piranos com aminas e álcoois - Barichello, Rosemario (2003)
This work presents the synthesis of α-alkylaminomethylene-γ- lactones 8 (one pot reaction) and α-alkylaminomethylene-δ-lactones 9 (two steps reaction), from the reaction of 3-trichloroacetyl-4,5-dihydrofuran (3) and 5- trichloroacetyl-3,4-dihydro-2H-pyran (4) respectively, with ammonium hydroxide and amines such as methylamine, ethylamine, propylamine, iso-propylamine, allylamine, ethanolamine, dimethylamine, diethylamine, pyrrolidine, piperidine and morpholine in dichloromethane or ethanol at room temperature for 1 hour, in good yields The 1,1,1-trihalo-3-hydroxyalkyl-4-alkylamino-3-buten-2-ones (5-7) were obtained in good yields from the reaction of 3-trihaloacetyl-4,5-dihydrofuran (1, 3) and 5-trihaloacetyl-3,4-dihydro-2H-pyran (2, 4) respectively, whit the same amines, in dichloromethane at room temperature for 1 hour. The reactions of 5- trichloroacetyl-3,4-dihydro-2H-pyran (4) with dimethylamine in the presence of alcohols, as solvent, furnished 3,4-dihydro-2H-piran-5-carboxylic esters 10.